Decentralization to enhance sustainable and equitable socioeconomic development - Padilla, Perfecto L. (1998)
Decentralization may and should enhance socioeconomic development without necessarily devastating the country's environment and natural resources. Sustainable and equitable development can be attained by strengthening and accelerating the implementation of devolved functions and services at the local government level, whereby the local government unit, the community, nongovernmental organizations, and the industrial sector cooperate in pursuing socioeconomic development, with a conscious thrust to protect the environment and conserve natural resources. Harmful effects and other direct and indirect consequences of industrial projects that might result in environmental degradation must be considered along with the benefits of the proposed activities so as to be able to prevent them. - Reproduced
Keywords: Decentralization - Philippines; Economic and social development - Philippines; Economic and social development